EPISTEMOLOGI TAFSIR TEMATIK KONTEMPORER BIDANG EKONOMI DI INDONESIA: Studi terhadap Tafsir Tematik karya M. Quraish Shihab - MUHAMMAD ANDI ROSA (Tazkiya, 2015)
The corpus of this research uses Quraish Shihab Works in four of Thematics Exegesis relating with economical sciences. The themes is: “Ribâ according to Qur‟an”, “islam and development”, “economy according to Qur‟an”, “the principal and foundation of islamic economy according to Qur‟an”. The researcher uses Content Analysis as the research methodology, with Qur‟anic methodology perspective especially in term manhaj al-tafsîr and tharîqat al-tafsîr. The main question is: how is the caracteristic found with thematic exegesis dealing with the themes of exegesis on economical sciences ?. The research findings reveal that, Epistemology analysis of Quraish Shihab Works in five Thematics Exegesis are, discovered 22 types of interpretation, and it can be classified to three types of analysis: a. Intrinsic Analysis (al-tahlîl mâ fî al-nash); b. Extrinsic Analysis (al-tahlîl mâ hawla al-nash), c. The analysis from previous theologian). This research shows that Quraish Shihab open to dialogue of economical sciences in Qur‟anic exegesis in theority and pratical, though is not maximum. So that, the ideal of purpose in theories of thematic exegesis, can not realization in his works of several thematic exegesis. In contextuality exegesis perspective, that the figure complies with the stipulations of contextual exegesis, and stipulations of Qur‟anic social exegesis.